ANALISIS PENDAPATAN USAHATANI POLA TANAM PADI-PADI DI DESA JEMBAYAN DALAM KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA - Mutiara Caesar Ningrum; Nella Naomi Duakajo; Mariyah Mariyah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
ABSTRACTThe agricultural sector plays an important role in people's daily food. Humans essentially need food crops as staples. The operation of a coal mining company around the area of Jembayan Dalam Village is claimed by farmers to pollute their fields and cause rice productivity to decline. Analyzes the income of farmers who perform a rice-rice crop rotation pattern in Jembayan Dalam Village, Loa Kulu District, Kutai Kartanegara Regency. The method used is the collection of data directly into the field by using Simple Random Sampling that 34 respondents then analyzed agricultural income with rice planting patterns on rice fields. Based on the results of research in Jembayan Dalam Village, Loa Kulu District, the average production cost in the growing season 1 is higher than the growing season 2 where in season 1 the average amount is Rp7,709,156.79/ha and in season 2 the average amount is Rp6,269,040.26/ha with an average per year of Rp13,978,197.04/ha. The average production on season 1 is higher than season 2 where the average season 1 is 1,393.24 kg and at season 2 the average is 642.35 kg with an annual average of 2,035.59 kg. The average acceptance on season 1 is higher than season 2 where the average season 1 is Rp9,100,142.97/ha and on season 2 the average is Rp4,184,263.07/ha with an annual average of Rp13,284,406.05/ha. Average revenue on season 1 is higher than season 2 where on season 1 the average amount is Rp1,390,986.19 ha and on season 2 the average is Rp-2,448,492.87/ha with an annual average of Rp-693,791.00/ha.